A Strategy for Discovering Heterochiral Bioactive Peptides by Using the OB2nP Library and SPOTs Method. (15th July 2019) - Udagawa, Hinako; Yoneda, Takato H.; Masuda, Ryo; Koide, Takaki
Abstract: d ‐Amino acid containing peptides are promising as drug lead compounds because of their expected higher stability in vivo. A heterochiral random peptide library called the one‐bead–2 n ‐peptide (OB2 n P) library, which can display 2 n peptide diastereomers per bead, has been developed. Through screening of the OB2 n P library and subsequent binding assay among the peptide diastereomers synthesized in parallel by means of the SPOTs method, new heterochiral mimotopes for the anti‐β‐endorphin monoclonal antibody have been obtained. One mimotope was a new ligand for the μ‐opioid receptor. The screening strategy enabledd ‐amino acid containing drug leads to be obtained efficiently by expanding searchable chemical space without increasing the experimental scale. Abstract : Split and mix : The one‐bead–2 n ‐peptide (OB2 n P) library, which displays 2 n diastereomers of an n ‐mer peptide per bead, enables efficient screening ofd ‐amino acid containing bioactive peptides. The combination of library screening and subsequent identification of the diastereomer(s) by using the SPOTs method offers a powerful strategy for lead generation in drug discovery.